2017
DOI: 10.1186/s12974-017-0829-2
|View full text |Cite
|
Sign up to set email alerts
|

Teriflunomide and monomethylfumarate target HIV-induced neuroinflammation and neurotoxicity

Abstract: HIV-associated neurocognitive disorders (HAND) affect about 50% of infected patients despite combined antiretroviral therapy (cART). Ongoing compartmentalized inflammation mediated by microglia which are activated by HIV-infected monocytes has been postulated to contribute to neurotoxicity independent from viral replication. Here, we investigated effects of teriflunomide and monomethylfumarate on monocyte/microglial activation and neurotoxicity. Human monocytoid cells (U937) transduced with a minimal HIV-Vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…In addition, it has been shown that the HMC3 cells (provided by Dr. J Pocock, University College of London) produce significant amounts of IL-6, together with several chemokines (i.e., CXCL10, CCL5, and CCL2) in response to human immunodeficiency virus (HIV) vector-transduced monocytoid cells (HIV-U937 cells). HMC3 microglial cells in contact with HIV vector alone responded with increased production of IL-6, CXCL10, and CCL5, albeit to a lower extent in comparison to activation with HIV-U937 cells [30]. Data presented in this paper confirm a basal production of IL-6 in HMC3 cells, together with sizable amounts of CCL5.…”
Section: Functional Properties Cytokine and Chemokine Productionsupporting
confidence: 69%
See 3 more Smart Citations
“…In addition, it has been shown that the HMC3 cells (provided by Dr. J Pocock, University College of London) produce significant amounts of IL-6, together with several chemokines (i.e., CXCL10, CCL5, and CCL2) in response to human immunodeficiency virus (HIV) vector-transduced monocytoid cells (HIV-U937 cells). HMC3 microglial cells in contact with HIV vector alone responded with increased production of IL-6, CXCL10, and CCL5, albeit to a lower extent in comparison to activation with HIV-U937 cells [30]. Data presented in this paper confirm a basal production of IL-6 in HMC3 cells, together with sizable amounts of CCL5.…”
Section: Functional Properties Cytokine and Chemokine Productionsupporting
confidence: 69%
“…Data presented in this paper confirm a basal production of IL-6 in HMC3 cells, together with sizable amounts of CCL5. Other cytokines, including IFNγ, IL-1β, IL-4, and IL-10 were not detected [30]. The immunomodulating agent, teriflunomide, significantly reduced microglial inflammatory activation induced by HIV-U937 cells, whereas, monomethylfumarate (MMF) was less effective (only CXCL10 reduction at the highest dose tested).…”
Section: Functional Properties Cytokine and Chemokine Productionmentioning
confidence: 97%
See 2 more Smart Citations
“…Guo et al () injected a retrovirus under the control of GFAP promoter in adult mouse cortex to specifically express NeuroD1, which is essential for adult neurogenesis (Gao et al, ; Zhang et al, ), in activated astrocytes. It is worth to mention that retroviruses only infect dividing cells such as progenitor cells or reactive glial cells (Ambrosius et al, ; Zhao, Teng, Summers, Ming, & Gage, ). NeuroD1‐expressing astrocytes can reprogram into glutamatergic neurons in AD mouse model and cultured human astrocytes in vitro (Guo et al, ).…”
Section: Astrocyte Pathology In Different Onsets Of Ndsmentioning
confidence: 99%